2010
DOI: 10.1002/jms.1864
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in MALDI‐TOF MS analysis of the low molecular weight human serum proteome

Abstract: The combination in advances in MALDI-TOF MS instrumentation(1) and serum sample preparation techniques,(2-4) has lead to the emergence of MALDI serum protein expression profiling as a promising tool for biomarker discovery.(5) However, three factors still pose significant challenges for MALDI profiling of serum: the limited mass window of MALDI, serum protein complexity,(6) and analytical reproducibility. (7,8) MALDI has a small mass preference due to the ionization efficiency of intact protein molecules and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…We confirmed that these factors were not influencing the accuracy of our approach based on the CVs detected. CVs reported in this study confirm similar reports from other research groups ( 17 , 23 , 24 ). In this study, we were interested in determining a specific protein or a panel of proteins that could be used for COVID-19 prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…We confirmed that these factors were not influencing the accuracy of our approach based on the CVs detected. CVs reported in this study confirm similar reports from other research groups ( 17 , 23 , 24 ). In this study, we were interested in determining a specific protein or a panel of proteins that could be used for COVID-19 prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…CVs reported in this study confirm similar reports from other research groups. 17,23,24 The overfitting issue, normally seen in these approaches, was minimized using independent datasets for the training and the validation. Moreover, the test dataset was analyzed only once based on the results from the training set avoiding subjective selection of the best results.…”
Section: Discussionmentioning
confidence: 99%
“…The technique is widely used in biomedical research to profile the distribution of proteins, peptides, and small molecules on tissue . In addition, MALDI‐IMS provides reproducible high‐resolution mass measurements of molecules in complex biological matrices such as cells and serum samples . MALDI‐IMS plays a key role in the discovery of biomarkers for the diagnosis of cancer and classification of the disease pathology .…”
mentioning
confidence: 99%
“…[4][5][6] In addition, MALDI-IMS provides reproducible high-resolution mass measurements of molecules in complex biological matrices such as cells and serum samples. [7,8] MALDI-IMS plays a key role in the discovery of biomarkers for the diagnosis of cancer and classification of the disease pathology. [9,10] Given its ability to localize proteins and smaller molecules across an entire tissue section, MALDI-IMS analysis holds promise in the elucidation of molecular processes in the tumor microenvironment.…”
mentioning
confidence: 99%